Untethered Recyclable Tubular Actuators with Versatile Locomotion for Soft Continuum Robots. Issue 29 (27th May 2018) - Qian, Xiaojie; Chen, Qiaomei; Yang, Yang; Xu, Yanshuang; Li, Zhen; Wang, Zhenhua; Wu, Yahe; Wei, Yen; Ji, Yan
Abstract: Stimuli‐responsive materials offer a distinguished platform to build tether‐free compact soft robots, which can combine sensing and actuation without a linked power supply. In the past, tubular soft robots have to be made by multiple components with various internal channels or complex cavities assembled together. Moreover, robust processing, complex locomotion, simple structure, and easy recyclability represent major challenges in this area. Here, it is shown that those challenges can be tackled by liquid crystalline elastomers with allyl sulfide functional groups. The light‐controlled exchange reaction between allyl sulfide groups allows flexible processing of tubular soft robots/actuators, which does not need any assisting materials. Complex locomotion demonstrated here includes reversible simultaneous bending and elongation; reversible diameter expansion; and omnidirectional bending via remote infrared light control. Different modes of actuation can be programmed into the same tube without the routine assembly of multiple tubes as used in the past. In addition, the exchange reaction also makes it possible to use the same single tube repeatedly to perform different functions by erasing and reprogramming. Abstract : Tubular soft actuators made of adaptable liquid crystalline elastomers are programmed in a facile way to show complex motions including simultaneous bending and elongation; diameter expansion; and omnidirectional bending. Different modes of actuation can be written on the same tube without manual assembly. The same tube can be repeatedly reprogrammed into new mode of locomotion.